Case report: Gastric carcinoma with SMARCA4 deficient: two cases report and literature review - Lin, Zeyang; Li, Qian; He, Yujie; Guo, Shujing; Ye, Yuhan; Liu, Zhengjin (Frontiers in Oncology, 2024)
SMARCA4-deficient gastric carcinoma has been reported sporadically since 2016. Only 29 patients have been reported; nevertheless, it is aggressive and highly malignant with poor outcomes. It has an immunohistochemical phenotype showing loss of SMARCA4 expression and can be accompanied by codeletion of other switch/sucrose non-fermentable chromatin-remodeling complex subunits. Microscopically, it displays high-grade undifferentiated histological morphology with rhabdoid cell differentiation. Rarely does the tumor contain a purely or partly adenocarcinoma component. Here, we report two cases to demonstrate these unusual morphologies analyzed using morphological and immunohistochemical techniques. In addition, there is a lack of research on the classification of these morphologies. Therefore, our report will aid the diagnosis and classification of SMARCA4-deficient gastric carcinoma.